Pelatihan Keterampilan Observasi Gaya Belajar Dalam Upaya Penanganan Permasalahan Siswa - Tinartayu, Seshy; Makiyah, SN Nurul; Suryandari, Galuh; Kurniawan, Muhammad; Nafi'ah, Fadila Nurun (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2024)
This research is based on the importance of the teacher's role in the teaching and learning process such as understanding student characteristics such as learning styles. The purpose of this research is to increase the ability to maximize human resources in students by understanding their learning styles so that they can create an effective teaching and learning environment. This community service was carried out at SMA Muhammadiyah III Yogyakarta which was attended by 41 teachers as participants. The results of this training show that the teacher's view of observing student learning styles increases and has a better understanding of the use of several methods to observe student learning styles, the benefits, and the importance of the teacher's role in maximizing student learning performance.